Unemployment duration and exit states in Britain - René Böheim; Mark P. Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2000)
This paper presents new evidence on the determinants of unemployment duration for men and women in Britain in the 1990s, using a nationally representative data set. It examines the impact of individual and local labour market characteristics on the probability of unemployment spells ending with moves into full and part-time employment, self-employment and economic inactivity. The data show that the median duration of unemployment spells among men, at five months, is almost double that for women, although much of this differential is explained by exits to part-time work and economic inactivity among women. Multivariate analysis suggests that policies to reduce unemployment duration and encourage full-time work, especially among men, should be targeted towards those aged 25 and over on entering unemployment and on increasing education levels. Mothers are found to have significantly lower exit rates into full-time work than both men and childless women.
Keywords: 330